VARIOUS METHODS AND SEASONAL VARIATION OF SUICIDE - A PROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2016)
Background: Suicide is considered one of the major health problems all over world in which India has one of the highest suicide rates among people of aged between 15 and 29 years. Aims and objective: To know different method of suicide in different age group and different gender and seasonal variation of suicide. Method: This prospective study was done in forensic medicine department of tertiary hospital in mid Gujarat region. Cases with alleged history of suicide were taken during period March-April 2013 to March-April 2014 and detailed structured questions were asked to relatives, friends, and investigating authorities. Result: Poisoning (45.5%) was the most common pattern of suicide followed by hanging (40.1%). Among other methods, Burns was preferred by female while cut throat and jump on rail track by male. The numbers of suicide cases were noted to be highest during spring (27.42%) and lowest during winter (20.81%) season. It was noted that in day pattern, on Monday maximum number of cases whereas cases were the least on Saturday. Conclusion: Our study revealed Males were more affected than females in suicide. Poisoning was the most common pattern of suicide and there was a considerable variation in suicide based on days of week as well as seasons of a year.
Keywords: Suicide; hanging; poisoning